2014
DOI: 10.1101/gad.228510.113
|View full text |Cite
|
Sign up to set email alerts
|

Zrf1 is required to establish and maintain neural progenitor identity

Abstract: The molecular mechanisms underlying specification from embryonic stem cells (ESCs) and maintenance of neural progenitor cells (NPCs) are largely unknown. Recently, we reported that the Zuotin-related factor 1 (Zrf1) is necessary for chromatin displacement of the Polycomb-repressive complex 1 (PRC1). We found that Zrf1 is required for NPC specification from ESCs and that it promotes the expression of NPC markers, including the key regulator Pax6. Moreover, Zrf1 is essential to establish and maintain Wnt ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 77 publications
0
52
0
Order By: Relevance
“…The requirement of AtZRF1a/b in maintaining H2Aub1 and H3K27me3 in Arabidopsis strongly contrasts with the known function of ZRF1 in H2Aub1 removal during the transcriptional induction of cell differentiation genes in mammalian embryonic cell lines (Richly et al, 2010;Aloia et al, 2014). It is generally known that the loss of PRC1/PRC2 function causes embryonic stem cells to differentiate into specific functional cell types in mammals but leads to the dedifferentiation of seedlings to form embryo-like tissues in Arabidopsis (Köhler and Villar, 2008;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The requirement of AtZRF1a/b in maintaining H2Aub1 and H3K27me3 in Arabidopsis strongly contrasts with the known function of ZRF1 in H2Aub1 removal during the transcriptional induction of cell differentiation genes in mammalian embryonic cell lines (Richly et al, 2010;Aloia et al, 2014). It is generally known that the loss of PRC1/PRC2 function causes embryonic stem cells to differentiate into specific functional cell types in mammals but leads to the dedifferentiation of seedlings to form embryo-like tissues in Arabidopsis (Köhler and Villar, 2008;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…The human ZRF1 protein has been reported to bind H2Aub1 via its UBD, to displace PRC1 from chromatin, and to favor H2Aub1 deubiquitination, leading to the switch from a repressive to an active chromatin state in the induction of PcG-silenced genes during teratocarcinoma cell differentiation (Richly et al, 2010). During the differentiation of mouse embryonic stem cells, ZRF1 specifically regulates the induction of master neural genes in a PcG-dependent manner and ZRF1 depletion impairs neural differentiation but not differentiation toward mesendodermal lineages (Aloia et al, 2014). Although ZRF1 homologs are found broadly present in the green lineage (Chen et al, 2014), their functions in relation to PcG silencing remain uncharacterized in higher plants so far.…”
mentioning
confidence: 99%
“…Moreover, H2AK119ub serves as a recruitment platform for Zrf1 (zuotin-related factor 1). Upon differentiation of NT2 cells (human teratocarcinoma cells) and ESCs, Zrf1 binds to H2AK119ub and displaces the PRC1 complex from chromatin, resulting in upregulation of lineage genes with differentiation (85,86).…”
Section: The Polycomb Group Of Proteins In Pluripotency and Differentmentioning
confidence: 99%
“…41,56 So far, Zrf1 was shown to primarily operate during differentiation into the neuronal lineage. [41][42][43] Notably, PRC1 silences a wide range of genes generating the 3 germ layers during development. 31 Hence, taking into account the broad spectrum of PRC1 target genes and the high abundance of H2A-ubiquitylation, we speculated that Zrf1 played additional roles in the formation of other germ layers.…”
Section: Discussionmentioning
confidence: 99%
“…41 Further, it was shown that Zrf1 is required to establish neural progenitor cells (NPCs) from mESCs and to maintain NPC self-renewal. 42 Neuronal differentiation triggered by Zrf1 is partially regulated by Id1, which interacts with Zrf1 and blocks its recruitment to chromatin. 43 Furthermore, the Zrf1 C. elegans ortholog dnj11 is involved in asymmetric cell division of neurosecretory motoneuron neuroblasts.…”
Section: 26mentioning
confidence: 99%